The Review of Household Agri-product Processing in Cambodia - Broem Koeun; Serey Mardy (International Journal of Sustainable Applied Sciences, 2023)
In Cambodia, domestic processing accounts for about 10% of total agricultural output, while processed agricultural exports make up only 8% of all official exports by value. Processing and handling of agricultural products after harvest need private investment if Cambodia is to benefit economically from adding value to its produce. There aren't many big businesses involved in agro-processing. Among the possible activities include the processing of dairy products, cashew nuts, sugar, fruits, fish products, meat, and cassava. Publicly available studies on Cambodian household agriproduct processing are also included in this review. An article based on literature research is this study. Food processing includes postharvest processing methods as well as packhouse, transport, market, and processing. The key to handling the issue of processing these productions is agro-processing. Items like candy, pickles, sausages, meatballs, fish balls, Prahok, frozen dairy, and soy milk, among others. The majority of agriculturally processed products are exported informally since they lack branding, packaging, certification, or licencing.  However, implementing agro-processing in Cambodia is fraught with difficulties involving labour, knowledge, machinery, equipment, and exporters' maintenance of the machinery.